2008
DOI: 10.1001/archinte.168.7.756
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Findings on Cardiac Multidetector Row Computed Tomography Among Healthy Older Adults<subtitle>Prevalence and Clinical Correlates</subtitle>

Abstract: Background: With the widespread use of cardiac multidetector row computed tomography (MDCT), the issue of incidental findings is receiving increasing attention. Our objectives were to evaluate the prevalence of incidental findings discovered during cardiac MDCT scanning and to identify clinical variables associated with incidental findings. Methods: This cross-sectional analysis involved a population-based sample recruited from an integrated health care delivery system in Northern California as part of the Ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 20 publications
4
28
0
2
Order By: Relevance
“…SPN of at least 5 mm size were found in 18% in the initial study collective. This ratio corresponds well to other published studies, which reported incidence rates ranging from 3.5% to 28% [9,[34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…SPN of at least 5 mm size were found in 18% in the initial study collective. This ratio corresponds well to other published studies, which reported incidence rates ranging from 3.5% to 28% [9,[34][35][36][37][38][39].…”
Section: Discussionsupporting
confidence: 92%
“…Nearly one in five cardiac computed tomography (CT) scans has been reported to show an incidental pulmonary nodule (1). In addition, the National Lung Screening Trial reported that 39% of high-risk smokers who underwent annual CT screening had a least one positive screening examination (2).…”
mentioning
confidence: 99%
“…Przypadkowo znalezione patologie pozasercowe mogą być odpowiedzialne za dolegliwości pacjenta i mogą mieć wpływ na dalsze postę-powanie lecznicze. Częstość wykrywania patologii pozasercowych w trakcie badania naczyń wieńcowych wynosi 15-90% [9][10][11][12][13][14][15][16][17], natomiast patologie istotne, które wymagają dalszej diagnostyki lub leczenia, stwierdzane są w 4,2-38% przypadków [9]. Tak duże różnice w częstości wykrywania patologii pozasercowych związane są przede wszystkim z typem skanera, na którym wykonywane były badania, jak również z zakresem badania (tętnice wieńcowe vs pomosty wieńcowe) (tab.…”
Section: Przypadkowe Znaleziska Pozasercoweunclassified
“…Jedną z najczęstszych patologii pozasercowych wykrywanych podczas badania CT naczyń wieńcowych są guzki w płucach. Ich częstość określana jest na 5-20% [15,18], najczęściej są to guzki poniżej 1 cm (9,3-19%), guzki większe od 1 cm wykrywane są w 0,6-2,4% przypadków [9,18] (ryc. 12.).…”
Section: Ct Scan Axial Image a -Large Atrial Septal Defect Type Ostunclassified